Prawa Człowieka . biuletyn, no. 6, 1989 - Komitet Helsiński w Polsce, [ed. Danuta Przywara, Marek A. Nowicki, Stefan Starczewski] (Oficyna Wydawnicza "Pokolenie", 1989)
Creation and circulation: From issue no. 9(1 grudnia 1990) published legally